The use of indocyanine green for lateral lymph node dissection in rectal cancer—preliminary data from an emerging procedure: a systematic review of the literature - Kehagias, D.; Lampropoulos, C.; Bellou, A.; Kehagias, I. (Techniques in coloproctology, 2024)
Introduction Lateral lymph node dissection (LLND) for rectal cancer is still not a widely established technique owing to the existing controversy between Eastern and Western countries and the lack of well-designed studies. The risk of complications and the paucity of long-term oncological results are significant drawbacks for further applying this technique. The use of indocyanine green (ICG) near-infrared (NIR) fluorescence for LLND appears as a promising technique for enhancing postoperative and oncological outcomes. This review aims to evaluate the emerging role of ICG during LLND and present the benefits of its application. Materials and methods Systematic electronic research was conducted in PubMed and Google Scholar using a combination of medical subject headings (MeSH). Studies presenting the use of ICG during LLND, especially in terms of harvested lymph nodes, were included and reviewed. Studies comparing LLND with ICG (LLND + ICG) or without ICG (LLND-alone) were further analyzed for the number of lymph nodes and postoperative outcomes. Results In total, 13 studies were found eligible and analyzed for different parameters. LLND + ICG is associated with significantly increased number of harvested lateral lymph nodes ( p < 0.05), minor blood loss, decreased operative time, and probably decreased urinary retention postoperatively compared with LLND-alone. Conclusions The use of ICG fluorescence during LLND is a safe and feasible technique for balancing postoperative outcomes and the number of harvested lymph nodes. Well-designed studies with long-term results are required to elucidate the oncological benefits and establish this promising technique.